2003
DOI: 10.1034/j.1600-0412.2003.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in women with pain and endometriosis

Abstract: In Norway there is a considerable delay in the diagnosis of endometriosis, with figures comparable to results from Anglo-American studies. A greater awareness of symptoms of endometriosis and a more rapid investigation should thus be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(133 citation statements)
references
References 6 publications
1
128
0
4
Order By: Relevance
“…4 A definitive diagnosis of endometriosis can only be made at surgery, generally via laparoscopy, and there are well-recognised risks associated with this. 5,6 Moreover, studies report that between 21 7 and 46% 8 of women with chronic pelvic pain are found not to have any identified pathology at laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…4 A definitive diagnosis of endometriosis can only be made at surgery, generally via laparoscopy, and there are well-recognised risks associated with this. 5,6 Moreover, studies report that between 21 7 and 46% 8 of women with chronic pelvic pain are found not to have any identified pathology at laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Az első tünetek jelentkezésétől számítva Németországban és Ausztriá-ban például átlagosan 10 év [15], Norvégiában 6 év [16], míg Magyarországon 3,9 év telik el [17]. Pedig a korai diagnózis fontos volna, mivel a gyakran igen súlyos panaszokat okozó mélyen infiltráló endometriosis kedvezőtlenül befolyásolja a betegek életminőségét, növeli az egészségügyi kiadásokat és a csökkent munkaképesség miatt jelentős gazdasági kihatása is van [18].…”
Section: Megbeszélésunclassified
“…Longer delays can occur when the symptoms begin in adolescence. 3,4 Aside from the variability in presentation, the major reasons for delays in diagnosis include the prevalence of pelvic pain symptoms in the community and a lack of awareness by many health professionals that the onset of symptoms often occurs in adolescence. However, it is widely recognised around the world that endometriosis is now the commonest cause of chronic pelvic pain in women in most industrialised societies.…”
Section: Assessing Women With Suspected Endometriosismentioning
confidence: 99%
“…Medical treatments for endometriosis usually improve fertility. 4. Danazol is one of the first-line treatments of choice for endometriosis.…”
Section: Referencesmentioning
confidence: 99%